Modelling and analysis of multi-junction solar cells to improve the conversion efficiency of photovoltaic systems - Das, Narottam; Al Ghadeer, A.; Islam, Syed (Institute of Electrical and Electronics Engineers Inc., 2014)
© 2014 ACPE. This paper presents modelling and analysis of multi-junction solar cells to improve the conversion efficiency of photovoltaic (PV) power generation systems. For this modelling, Matlab/Simulink tool is used to obtain the simulation results. The modelling of a single junction solar cell can be performed by single or double diode models. From the simulation results, it was found that the double diode model is more accurate than the single diode model. Hence, the double diode model is used to simulate dual and triple junction solar cells. The simulations were performed under varying the critical factors, such as temperature and solar irradiance. The effect of these factors was clearly demonstrated on the I-V and P-V characteristics of the solar cells. It was found that the temperature increases, short circuit current increases slightly and open circuit voltage drops significantly. Consequently, the PV power generation decreases considerably. However, when the irradiance increases, the short circuit current increases slightly and the open circuit voltage increases significantly. Consequently, the power generation increases considerably and the conversion efficiency increases of the PV systems.